Violence: a growing danger to children the american case - Sayre, James W. (The Turkish Journal of Pediatrics, 1994)
A frightening, growing epidemic of senseless, irrational and inexcusable violence has seized the United States. While it involves all ages and localities, the occurrences are predominantly in areas of poverty, poor housing and unemployment. Children, particularly the adolescent and young adult male black population, are at greatest risk. There are recognized many contributing forces such as low self-esteem, family disruption and single parenting. Country-wide there is easy access to guns and lack of gun safety guards. Violent television sets an example for our youth and lends an air of adventure and excitement to their lives. The solution to this enormous problem is clearly not an easy one and must be through a combination of many social and legal changes. This is most assuredly a medical problem and demands thought and active participation by physicians. There are a number of strategies for physicians, especially pediatricians. We must look carefully at family interactions, attempting to promote more kindly behaviors, enhance self-esteem. School-age children can be helped through office discussions and collaboration with teachers. "Leave the knives and guns at home, avoid noisy arguments, use more kindly words." "Television is not real life; the actors do not die." These are our people. Their needs are great. We must help.